Impact of dyskinesia on activities of daily living in Parkinson's disease: Results from pooled phase 3 ADS-5102 clinical trials. (March 2019) - Pahwa, Rajesh; Isaacson, Stuart; Jimenez-Shaheed, Joohi; Malaty, Irene A.; Deik, Andres; Johnson, Reed; Patni, Rajiv
Abstract: Introduction: In Parkinson's disease, dyskinesias result from disease progression and chronic levodopa therapy. Using Unified Dyskinesia Rating Scale (UDysRS) data pooled from two pivotal trials of ADS-5102 (amantadine) extended-release capsules in dyskinetic patients, we assessed the impact of dyskinesia on activities of daily living (ADLs), and the effects of ADS-5102 versus placebo. Methods: Patients had troublesome dyskinesia (≥1 h/day) and at least mild functional impact of dyskinesia per Movement Disorder Society Unified Parkinson's Disease Rating Scale, Part IV, item 4.2. UDysRS Parts 1B, 3, and 4 scores at baseline were summarized descriptively. Twelve-week changes in score distributions and total scores were tested for significant differences between treatments. Results: Among 196 patients, the majority (63%–73%) characterized their dyskinesia at baseline as having at least a mild impact on walking and balance ; public and social settings ; exciting or emotional settings ; doing hobbies and other activities ; handwriting ; and dressing (six of ten ADLs in UDysRS Part 1B). By clinician ratings (in Parts 3 and 4), greatest impairment was most often observed in the trunk (62% of patients) and occurred most often for the ADL of dressing (64% had at least moderate impairment). ADS-5102 significantly reduced the patient-rated impact of dyskinesia on six of ten ADLs in Part 1B, the clinician-rated intensity of dyskinesia in all seven body regions assessed in Part 3, and the clinician-rated disability during three of four ADL tasks assessed in Part 4. Improvements in Parts 1B, 3, and 4 total scores were also statistically significant. Conclusion: Dyskinesia can impair multiple tasks of daily living. Further studies may help characterize its underreported impact. By several measures, ADS-5102 treatment was associated with significant improvement of dyskinesias. Highlights: Patients and physicians may fail to appreciate the impact of dyskinesias on daily life. UDysRS data at baseline were evaluated from 2 randomized clinical trials. Patients characterized their dyskinesia as negatively impacting many daily activities. Treatment with ADS-5102 attenuated the impact of dyskinesia on many of these daily activities.